THE PSYCHOLOGICAL ANALYSIS OF MAJOR CHARACTER OF THE BOY IN THE STRYPPED PYJAMAS MOVIE - Imam Safrudi (LPPM Universitas Bina Sarana Informatika, 2014)
Movie or film is considered as a powerful method or tool to influence people and delivering interest. As a powerful method for delivering interest. Meanwhile the characters play very important roles in the story, especially the major character. As the central figure of the story, the major character is the most significant character which controls the plot of the story. movie or film has messagesthat are implied through narratives presentation and its form to make people accept and embrace the messages. “THE BOY IN THE STRIPPED PYJAMAS” is a movie that wants to deliver a message about two innocent children in family life. Bruno and Shmuel consider each other that their fathers are good father. Analysis on the major characters in the movie shows that children who desire tomake their faculty is given. The children (Bruno, Shmuel) feel that their parents had not fulfilled their faculty. It often depicted in this movie, friendship, cruelty and risk making a wrong choice. Therefore, the aims of the analysis are (1). To find the five major characters in the mobie,(2). To analyze the characterization of the major characters, (3). To analyze the children characters’ condition through psychological perspective.